Пьесы для ансамблей семиструнных гитар: [в 5 выпусках] - Мелешко Ромуальд Феликсович (1964)
Экземпляры: ИСК (20231125) / Инвентарный номер: / Сис.шифр: 85.952.6 / Авт.знак: П 96 / ГРНТИ: 18.41 / ББК: 85.952.634